2005
DOI: 10.1016/j.bone.2004.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between compressive properties of human os calcis cancellous bone and microarchitecture assessed from 2D and 3D synchrotron microtomography

Abstract: The aim of this study was to determine the contribution of 2D and 3D microarchitectural characteristics in the assessment of the mechanical strength of os calcis cancellous bone. A sample of cancellous bone was removed in a medio-lateral direction from the posterior body of calcaneus, taken at autopsy in 17 subjects aged 61-91 years. The sample was first used for the assessment of morphological parameters from 2D morphometry and 3D synchrotron microtomography (ACT) (spatial resolution = 10 Am). The 2D morphome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 61 publications
(77 reference statements)
1
17
0
Order By: Relevance
“…Many studies have reported FEM investigation of biomechanical properties of bone microstructure from microCT [65,66]. In a recent work, SR microCT images were used to simulate acoustic propagation in view of a better understanding of ultrasonic parameters [67].…”
Section: Studies By Microctmentioning
confidence: 99%
“…Many studies have reported FEM investigation of biomechanical properties of bone microstructure from microCT [65,66]. In a recent work, SR microCT images were used to simulate acoustic propagation in view of a better understanding of ultrasonic parameters [67].…”
Section: Studies By Microctmentioning
confidence: 99%
“…There are numerous data over the last 20 years characterizing age, gender, and anatomic differences in cadaveric specimens of bone [13, 45, 52, 64, 67, 68, 94]. Clinical applications generally preclude access to the most relevant sites, such as the spine and proximal femur.…”
Section: Introductionmentioning
confidence: 99%
“…As previously published (Cendre et al, 1999;Follet et al, 2005) unconstrained compressive testing was performed on calcaneus trabecular specimens (cube of 9 Â 9 Â 9 mm 3 , Schenck RSA 250, Fig. 3).…”
Section: Compressive Testsmentioning
confidence: 99%